(untitled) (International Journal of Engineering and Computer Science, 2017)
Event marketing is growing at a rate of three times that of traditional advertising. Though relatively small compared to the major components of the marketing communications mix-advertising, sales promotions and point-of-purchase merchandisingexpenditures on event sponsorship are increasing. Event marketing is growing rapidly because it provides companies alternatives to the cluttered mass media, ability to segment on a local or regional basis, and opportunities for reaching narrow lifestyle groups whose consumption behavior or entertainment can be linked with the local event. Event Finder is a website specializing in Event marketing primarily targeting college students, recent graduates, and young professionals. This proposed system allows users to find events. In this system, every event manager has their own login and they can upload the event details. Event details will be sent to external users through SMS based on their area of interests.